2012
DOI: 10.4045/tidsskr.10.1273
|View full text |Cite
|
Sign up to set email alerts
|

Organdonasjon og norske legers behov for opplæring

Abstract: Background. The skill of the person who inquires about organ donation and the timing of the conversation may have an impact on the likelihood of obtaining consent from a patient's next of kin. The purpose of the study was to investigate the experience that intensive care doctors and neurosurgeons have of relating to organ donors or communicating with their next of kin, as well as the doctors' own learning needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
1
0
4
Order By: Relevance
“…They concluded that training programs should focus on communication regarding organ donation with the caregivers of patients. [8] Tam et al . administered a questionnaire regarding knowledge, attitudes and commitment toward organ donation to nursing students.…”
mentioning
confidence: 99%
“…They concluded that training programs should focus on communication regarding organ donation with the caregivers of patients. [8] Tam et al . administered a questionnaire regarding knowledge, attitudes and commitment toward organ donation to nursing students.…”
mentioning
confidence: 99%
“…Studiens begrensninger er tidligere omtalt (10). Svarprosenten er lav, og det er rimelig å anta at de med størst interesse for og kompetanse på organdonasjon kan vaere overrepresentert.…”
Section: Begrensningerunclassified
“…Dersom organdonasjon er aktuelt, skal spørsmålet om organdonasjon tas opp med de pårørende (5). Flere faktorer er ansett som viktige for å få tilsagn til organdonasjon: god kommunikajon med pårørende (10), helsepersonellets kompetanse og holdning til organdonasjon (11,12) og at de pårørende har forstått hva opp-hevet cerebral funksjon innebaerer (12). Avslagsfrekvensen har de siste ni årene variert fra 17 % til 33 % (13).…”
unclassified
See 2 more Smart Citations